The Contribution of Archimedes in Greek Mathematics After Euclid to the Advancement of Modern Mathematics: Implications for Student Understanding - Nadira, Khaisa Alifa; Harisman, Yulyanti (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study examines Archimedes' contributions to the development of Greek mathematics after Euclid and its impact on the advancement of modern mathematics, as well as its implications for students. Although his contributions have been widely discussed, a deep understanding of the relevance of Archimedes' principles to modern mathematics is still limited. The purpose of this study is to analyze Archimedes' contributions and their implications across various fields of mathematics and their contemporary applications. The research method used is descriptive qualitative with a literature review approach to understand Archimedes' contributions within the historical context and modern relevance. The instruments used are relevant scholarly literature, including books and journals. The literature review includes previous works that highlight Archimedes' contributions to mechanics and mathematics, particularly in areas such as geometry, calculus, and the understanding of volume and surface area. The data analysis technique applied is descriptive qualitative analysis to identify patterns and themes in Archimedes' contributions, such as his development of methods for calculating areas and volumes of geometric bodies, as well as his innovative work in fluid mechanics. The results of this study emphasize the importance of historical understanding of Archimedes' contributions to mathematics and their implications for students. This study encourages students to explore the historical roots of modern mathematical concepts, fostering a deeper appreciation for the evolution of mathematical thought. The implications and benefits of this study motivate students to develop critical thinking and innovative problem-solving skills, applying mathematical concepts in real-world contexts.